2019
DOI: 10.3389/fmicb.2019.02095
|View full text |Cite
|
Sign up to set email alerts
|

A Metabarcoding Analysis of the Mycobiome of Wheat Ears Across a Topographically Heterogeneous Field

Abstract: Plant associated microbial communities have recently received a lot of attention because thought to play a fundamental role in plant health and development. Focusing on cultivated crops, optimized farming practices must consider the role of these communities when aiming at reducing the impact of pathogens and increasing yields. Typical inhabitants of plant’s phyllosphere are bacteria and microscopic fungi, some of them pathogenic for the plant and dangerous for the consumers, due to the production of toxins. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…Among them, Zymoseptoria tritci , Microdochium nivalis , Gibellulopsis piscis , Mycosphaerella tassinia , Stemphylium vesicarium , Fusarium poae , F. graminearum , F. tricinctum , and F. langsethiae were detected. We confirmed that this zymogenic community has been inherited from the wheat plant, as reported previously [ 8 , 49 ]. Although wheat residues were buried in the soil after tillage (before 30- and 60-day sampling), the colonizing pathogens continued to be detected in large numbers throughout the first 60 days of straw decomposition, in both ambient and future climate treatments.…”
Section: Discussionsupporting
confidence: 92%
“…Among them, Zymoseptoria tritci , Microdochium nivalis , Gibellulopsis piscis , Mycosphaerella tassinia , Stemphylium vesicarium , Fusarium poae , F. graminearum , F. tricinctum , and F. langsethiae were detected. We confirmed that this zymogenic community has been inherited from the wheat plant, as reported previously [ 8 , 49 ]. Although wheat residues were buried in the soil after tillage (before 30- and 60-day sampling), the colonizing pathogens continued to be detected in large numbers throughout the first 60 days of straw decomposition, in both ambient and future climate treatments.…”
Section: Discussionsupporting
confidence: 92%
“…Fusarium species are generally distributed across fields and often infest large regions when conditions are suitable [4][5][6][7]. Within large wheat fields, Fusarium species concentrate in areas with a more humid and, thus, usually cooler microclimate [8,9]. Therefore, higher Fusarium species abundances are observed mainly in spots with higher plant productivity and higher canopy cover [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The colour scale illustrates the dominance (%) within the sites. The dendrogram on top illustrates the similarity of the sites; the one on the left represents the similarity in the pattern of occurrence of the individual fungal OTUs and Corlett 2019; Egidi et al 2019;Epstein et al 2019;Li et al 2019;Lynikiene et al 2020;Morales-Rodriguez et al 2019;Nerva et al 2019;Qian et al 2020;Ricks and Koide 2019;Saravesi et al 2019;Wilkinson et al 2019;Würth et al 2019;Yao et al 2019;Zhang et al 2019), others strongly recommended the use of ITS1 (Mbareche et al 2020), as it had already been implemented in many studies (Beule et al 2019;Checinska Sielaff et al 2019;Del Frari et al 2019;Schiro et al 2019). Few studies are based on both ITS regions (Janakiev et al 2019).…”
Section: Applied Methodsmentioning
confidence: 99%